Analisis Sensitivitas Struktur Anjungan Lepas Pantai di Bawah Kedalaman Gerusan yang Bervariasi - Suarjana, Made; Kiesin, Willy (Jurnal Teknik Sipil, 2024)
Several offshore platforms operating in the Java Sea have reported experiencing scour at varying depths, raising concerns about the safety and integrity of these structures. Scouring, an erosion phenomenon that occurs around these offshore platform structures due to their presence, is one of the most common issues encountered. The presence of scour can have a significant impact on the safety of these structures. To comprehend the implications of scour on structural safety, sensitivity analysis proves to be an invaluable tool. Sensitivity analysis establishes a relationship between changes in the safety parameters of the structure, obtained through linear analysis, and the depth of scour. By investigating this connection, sensitivity curves can be generated, enabling a conservative prediction of alterations in the strength parameters of the structure due to scour. In this study, a four-legged jacket platform structure underwent linear analysis under storm and seismic conditions using the SACS software. The scour phenomenon was simulated by adjusting the mudline's elevation beneath the structure, modifying the pile coordinates, reducing the length of piles beneath the mudline, and accounting for soil characteristics at each scour depth in the model. The sensitivity analysis revealed that the safety factors of the upper structural components, connections, and piles decrease at varying rates corresponding to each component type as the scour depth of the platform increases. By implementing these sensitivity curves, engineers and operators can make informed decisions regarding the maintenance and retrofitting of offshore platform structures to ensure their ongoing safety and structural integrity in the face of scour-related challenges. This research provides valuable insights into the critical relationship between scour depth and structural safety, enhancing our ability to protect offshore operations in the Java Sea and similar environments.